Augmented Ouabain-Induced Vascular Response Reduces Cardiac Efficiency in Mice with Migraine-Associated Mutation in the Na+, K+-ATPase α2-Isoform - Rajkumar Rajanathan; Tina Myhre Pedersen; Halvor Osterby Guldbrandsen; Lenette Foldager Olesen; Morten B. Thomsen; Hans Erik Bøtker; Vladimir V. Matchkov (Biomedicines, 2023)
Heterozygous mice (α2+/G301R mice) for the migraine-associated mutation (G301R) in the Na+,K+-ATPase α2-isoform have decreased expression of cardiovascular α2-isoform. The α2+/G301R mice exhibit a pro-contractile vascular phenotype associated with decreased left ventricular ejection fraction. However, the integrated functional cardiovascular consequences of this phenotype remain to be addressed in vivo. We hypothesized that the vascular response to α2-isoform-specific inhibition of the Na+,K+-ATPase by ouabain is augmented in α2+/G301R mice leading to reduced cardiac efficiency. Thus, we aimed to assess the functional contribution of the α2-isoform to in vivo cardiovascular function of wild-type (WT) and α2+/G301R mice. Blood pressure, stroke volume, heart rate, total peripheral resistance, arterial dP/dt, and systolic time intervals were assessed in anesthetized WT and α2+/G301R mice. To address rate-dependent cardiac changes, cardiovascular variables were compared before and after intraperitoneal injection of ouabain (1.5 mg/kg) or vehicle during atrial pacing. The α2+/G301R mice showed an enhanced ouabain-induced increase in total peripheral resistance associated with reduced efficiency of systolic development compared to WT. When the hearts were paced, ouabain reduced stroke volume in α2+/G301R mice. In conclusion, the ouabain-induced vascular response was augmented in α2+/G301R mice with consequent suppression of cardiac function.